Fluorinated Olefinic Lactams: The Case of Amino Acids – Preparation and Mechanistic Studies - Salamon-Krokosz, Katarzyna; Gołdyn, Mateusz; Siodła, Tomasz; Bartoszak-Adamska, Elżbieta; Koroniak, Henryk; Koroniak-Szejn, Katarzyna (Synthesis, 2022)
Herein, we report the synthesis of analogues of amino acids with a monofluorovinyl moiety. Interestingly, we have found that cyclization of the obtained products proceeds easily in all cases. The cyclization process has not previously been observed at this reaction stage, and such fluorinated lactams derived from phenylalanine, valine, alanine have not been described before.
Keywords: amino acids; monofluorovinyl; cyclization; peptidomimetics; fluorinated lactam